Lenalidomide maintenance therapy in previously treated chronic lymphocytic leukaemia (CONTINUUM): a randomised, double-blind, placebo-controlled, phase 3 trial. Issue 11 (November 2017) - Chanan-Khan, Asher A; Zaritskey, Andrey; Egyed, Miklos; Vokurka, Samuel; Semochkin, Sergey; Schuh, Anna; Kassis, Jeannine; Simpson, David; Zhang, Jennie; Purse, Brendan; Foà, Robin
Summary: Background: The efficacy and safety of lenalidomide as maintenance therapy after chemotherapy-based second-line therapy in patients with chronic lymphocytic leukaemia is unknown. Although kinase inhibitors can improve outcomes for some patients with relapsed and refractory disease, not all patients have access to these novel drugs. In this study, we aimed to assess the efficacy and safety of lenalidomide as maintenance therapy in patients with previously treated chronic lymphocytic leukaemia. Methods: This randomised, double-blind, placebo-controlled, phase 3 trial (CONTINUUM) was done at 111 hospitals, medical centres, and clinics in 21 countries. Patients were eligible if they had chronic lymphocytic leukaemia; were aged 18 years or older; had been treated with two lines of therapy (with at least a partial response after second-line therapy); had received a purine analogue, bendamustine, anti-CD20 antibody, chlorambucil, or alemtuzumab as first-line or second-line treatment; and had an Eastern Cooperative Oncology Group performance score of 0–2. Eligible patients were randomly assigned (1:1) by an interactive voice-response system to receive either oral lenalidomide (2·5 mg/day) or matching oral placebo capsules (2·5 mg/day) for 28-day cycles, until disease progression or unacceptable toxicity. Lenalidomide dose escalation (to 5 mg or 10 mg per day) was permitted if the drug was well tolerated. Patients, investigators, and those completing data analyses were masked to treatment allocation. Randomisation was stratified by age, response to second-line therapy, and prognostic factors. Co-primary endpoints were progression-free survival and overall survival; the primary endpoint was later changed to overall survival after the data cutoff for this analysis. Secondary endpoints were time from randomisation to second disease progression or death (PFS2), 32 tumour response (improvement in response and duration of response), safety, and health-related quality of life (HRQoL). Efficacy analyses were done in the intention-to-treat population. Safety was analysed in all patients who received at least one dose of study drug. This trial is registered withClinicalTrials.gov, numberNCT00774345, and is closed to accrual, but follow-up is ongoing. Findings: Between Feb 16, 2009 and Sept 29, 2015, 314 patients with chronic lymphocytic leukaemia were enrolled and randomly assigned to receive either lenalidomide (n=160) or placebo (n=154). With a median follow-up of 31·5 months (IQR 18·9–50·8), there was no significant difference in overall survival between the lenalidomide and the placebo groups (median 70·4 months, 95% CI 57·5–not estimable [NE] vs NE, 95% CI 62·8–NE; hazard ratio [HR] 0·96, 95% CI 0·63–1·48; p=0·86). Progression-free survival was significantly longer in the lenalidomide group (median 33·9 months, 95% CI 25·5–52·5) than in the placebo group (9·2 months, 7·4–13·6; HR 0·40, 95% CI 0·29–0·55; p<0·0001). PFS2 was significantly longer in the lenalidomide group than in the placebo group (median 57·5 months [47·7–NE] vs 32·7 months [26·4–49·0]; HR 0·46, 95% CI 0·29–0·70; p<0·01). Improved responses from baseline were observed in ten (6%) of 160 lenalidomide-treated patients versus four (3%) of 154 placebo-treated patients (p=0·12). Median time to improved response was 12·2 weeks (IQR 7·2–22·5) in the lenalidomide group versus 76·3 weeks (20·2–182·6) in the placebo group. Duration of improved response was not estimable in either group (95% CI 22·9–NE in the lenalidomide group vs NE–NE for placebo). There were no clinically meaningful differences in HRQoL between lenalidomide-treated patients and placebo-treated patients, as measured by FACT-Leu and EQ-5D, during maintenance treatment. In the safety population, the most common grade 3 or 4 adverse events included neutropenia (94 [60%] of 157 patients in the lenalidomide group vs 35 [23%] of 154 patients in the placebo group), thrombocytopenia (26 [17%] vs ten [6%]), and diarrhoea (13 [8%] vs one [<1%]). There were five fatal adverse events (three [2%] patients in the lenalidomide group and two [1%] patients in the placebo group). Interpretation: Lenalidomide might delay time to subsequent therapy and does not adversely affect response to subsequent therapy. Chemoimmunotherapy followed by lenalidomide maintenance could be an effective treatment option for patients with chronic lymphocytic leukaemia who do not have access to kinase inhibitors. Funding: Celgene Corporation.